2016
DOI: 10.3389/fnhum.2016.00619
|View full text |Cite
|
Sign up to set email alerts
|

Affective Priming by Eye Gaze Stimuli: Behavioral and Electrophysiological Evidence

Abstract: The present study employed the affective priming paradigm and measurements of event-related potentials (ERPs) to investigate implicit affective reactions elicited by gaze stimuli. Participants categorized positive and negative words primed by direct gaze, averted gaze and closed eyes. The behavioral response time (RT) results indicated that direct gaze implicitly elicited more positive affective reactions than did closed eyes. Analyses of the ERP responses to the target words revealed a priming effect on the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
(103 reference statements)
3
10
0
Order By: Relevance
“…Therefore, the present psychophysiological results are interpreted to indicate that direct gaze, relative to downward gaze, is automatically perceived as a more positive social signal, thus attenuating the startle reflex to intense sound stimuli. These results and conclusions are in line with those from our previous studies using the affective priming paradigm (Chen, Helminen, & Hietanen, 2017;Chen, Peltola et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, the present psychophysiological results are interpreted to indicate that direct gaze, relative to downward gaze, is automatically perceived as a more positive social signal, thus attenuating the startle reflex to intense sound stimuli. These results and conclusions are in line with those from our previous studies using the affective priming paradigm (Chen, Helminen, & Hietanen, 2017;Chen, Peltola et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in accord with previous studies showing that live faces with direct gaze were evaluated as less positive and more arousing than those with averted gaze and closed eyes (Hietanen et al, 2008;P€ onkänen, Alhoniemi et al, 2011). Thus, compatible with previous studies (Chen, Helminen, & Hietanen, 2017;Chen, Peltola et al, 2016), the present results also showed that implicit (physiological) and explicit (self-evaluative) affective responses to another's gaze direction may not always be fully concordant.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to show specifically the effect of another person's gaze direction on a perceiver's facial EMG responses. Considering that zygomatic responses have been associated with the occurrence of positive emotional reactions (Dimberg, 1990;Larsen et al, 2003;Tassinary & Cacioppo, 1992), the results can be interpreted to be compatible with previous studies employing implicit and explicit behavioral measures and reporting that direct gaze stimuli elicit more positive reactions than averted gaze or closed eyes stimuli (Chen et al, 2016;Chen, Helminen, et al, 2017;Chen, Peltola et al, 2017;Kuzmanovic et al, 2009;Lawson, 2015;Mason et al, 2005). As noted above, the zygomatic responses to another's direct vs. averted gaze were greater both when the participant was looking at the model and when the participant's own gaze was slightly turned away from the model.…”
Section: Running Head: Affiliative Eye Contact 20supporting
confidence: 89%
“…Compatible with these considerations, previous research has Running head: AFFILIATIVE EYE CONTACT 4 shown, for example, that seeing another person with direct as compared to averted gaze elicits increased electroencephalographic, relative left-sided frontal alpha activity associated with positive affect and motivational approach tendency (Hietanen, Leppänen, Peltola, Linna-aho, & Ruuhiala, 2008;Pönkänen, Peltola, & Hietanen, 2011). Two recent studies employing the affective priming paradigm indicated that more positive affective reactions were automatically activated by perception of direct gaze compared to perception of closed eyes (Chen, Helminen, & Hietanen, 2017;Chen, Peltola, Ranta, & Hietanen, 2016), and a study relying on the implicit association paradigm showed a robust preference for faces looking towards as compared to faces looking away (Lawson, 2015). Most recently, a study employing the startle reflex methodology reported that the magnitudes of participants' eyeblink startle and cardiac reflexes elicited by high-intensity noise stimuli were modulated by simultaneously presented gaze direction stimuli (Chen, Peltola, Dunn, Pajunen, & Hietanen, 2017).…”
Section: Introductionmentioning
confidence: 99%